The High Inspectorate of Education in legislative discussion. Significance and configuration need - Montero Alcaide, Antonio (Avances en Supervisión Educativa, 2022)
The High Inspectorate of Education has not been the subject of deep analyses or studies, although, due to jurisdictional and political conflicts that seem to require the exercise of its powers, it acquires a conjunctural interest. Despite an almost non-existent previous work on its object, this article focuses on the positions, contributions and justifications verified in the legislative processing of the different regulations affecting it given its basic character since its appearance in the legislation orbit. In addition, the author will also consider the different and specific initiatives and proposals made in this subject matter. Consequently, he proceeds to a documentary analysis focused on the amendments presented to the projects of the successive educational laws and the arguments motivating them. In doing so, he will be able to see the positions and perspectives adopted facing the uncertain and controversial future of the High Inspectorate of Education. The conclusions are related, then, to the relevance of the High Inspection itself, in confluence or differentiation with the Educational Inspection assumed by the Autonomous Communities – hence the relevance of the scope of intervention – as well as to the functions attributed to it, which are directly swayed or determined by the conditions of application themselves. As a result, the need of a basic regulation that is as essential as it is delayed and, presumably, hard to achieve.